2004
DOI: 10.21000/jasmr04011434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wildlife Utilization on Wyoming Big Sagebrush Growth and Survival on Reclaimed Mine Lands

Abstract: Ensuring Wyoming big sagebrush (Artemisia tridentata Nutt. ssp. wyomingensis Beetle & Young) survival remains a challenge on many mines even years after initial establishment. Wildlife utilization may be a major influence on its survival. A wildlife exclosure was erected in June 2001 on a portion of a study initiated in 1990 at the North Antelope/Rochelle Mine in northeastern Wyoming. Investigations focused on the influence of wildlife utilization on big sagebrush survival and growth under 3 grass seeding rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Our initial reports on seedling densities (Williams et al, 2002) suggested that sagebrush densities were only minimally influenced by grass seeding rates, agreeing with other studies (Johnson & Payne, 1968;Gores, 1995;Quinney et al, 1996;Booth et al, 1999;Partlow et al, 2004). However, our study emphasizes two things: the importance of long-term data collection on studies involving plant community dynamics and the apparent increased influence of grass seeding rates on sagebrush growth as the vegetation matures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our initial reports on seedling densities (Williams et al, 2002) suggested that sagebrush densities were only minimally influenced by grass seeding rates, agreeing with other studies (Johnson & Payne, 1968;Gores, 1995;Quinney et al, 1996;Booth et al, 1999;Partlow et al, 2004). However, our study emphasizes two things: the importance of long-term data collection on studies involving plant community dynamics and the apparent increased influence of grass seeding rates on sagebrush growth as the vegetation matures.…”
Section: Discussionsupporting
confidence: 90%
“…Wildlife browse can significantly reduce shrub size and survival Partlow et al, 2004). Wildlife use of sagebrush at our site was minimal and browsing was not common.…”
Section: Discussionmentioning
confidence: 81%
“…However, the effects of CBM wells last much longer. Although regulations require developers to attempt to reestablish the native vegetation (Wyoming Department of Environmental Quality, 1996), efforts to restore sagebrush communities are often unsuccessful (Olson et al, 2000; Partlow et al, 2004; Bergquist et al, 2007; Prevéy et al, 2009). Directional drilling, solar powered stations, and preventing further development surrounding areas supporting large, active leks may reduce the footprint of CBM development within the PRB.…”
Section: The Casementioning
confidence: 99%